Parent's awareness towards escalators accidents involving children safety at shopping complex / Nur Rashidah Mohd Baharudin - Nur Rashidah, Mohd Baharudin (2018)
An escalator is a moving staircase which its function is to carry people between floors in a building. It can move large numbers of people without having to wait except during very heavy traffic. Department of Occupational Safety and Health (DOSH) conducted a research to enhance safety on the escalator in the wake of the latest incident. The department said between 2011 and May last year, it recorded 31 accidents nationwide involving escalators, with 97% of the victim being young children (New Strait Times, 2016). The aim of this research is to investigate the level of awareness of parents towards escalator accident involving children at shopping complex. In order to make the aim become successful, the objectives are to determine the level awareness of parents towards escalators accidents involving children safety in shopping complex, to identify the contributing factors of escalator accident and to suggest solution to improve safety of escalator in shopping complex. The scope of this research will focus on Pyramid shopping complex, Midvalley and also Berjaya Times Square. Questionnaire is used to achieve the objectives. The questionnaire was distributed to the parents who bring their children in the shopping complex. The data were analyzed by using SPSS software version 23.0. There are many factors that contribute to accident of escalator. According to Al-Sharif (2006) the factor that can be contributed to accident of the escalator is poor design including location and environment, poor maintenance, lack of inspections or bad operations of the escalator, poor design and also bad passenger behavior. Then, according by HSE (2011), there are many solutions to reduce accident of escalator such as operationally daily safety checks, cleaning and preventive maintenance, routine cleaning and deep cleaning, cleaning for internal area, regular preventive maintenance and also check the lighting level, signage and the warning devices.